Veterinary Research - Brémont, Michel
Veterinary Research is an open access journal that publishes high quality and novel research and review articles focusing on all aspects of infectious diseases and host-pathogen interaction in animals. Food animals, companion animals, equines, wild animals (if the infections are of zoonotic interest and/or in relation with domestic animals), laboratory animals and animal models of human infections are considered. Studies on zoonotic and emerging infections are highly appreciated. Topics published by the journal include: New knowledge on pathogens (viruses, bacteria, protozoa, helminths, fungi and prions) and on host-pathogen interactions. Papers elucidating molecular mechanisms of interactions between hosts and microbes are highly appreciated. Immunity to pathogenic micro-organisms and systemic and mucosal immunology of infected organisms. This topic encompasses fundamental studies on the immune system of animals. The development and evaluation of new vaccines against pathogens will be considered. Epidemiological papers should provide new knowledge on pathogen-host interactions and/or host-population interactions related to infectious diseases. Manuscripts dealing with spread and/or transmission dynamics of infectious diseases will be favoured. Studies using mathematical modelling and developing or applying new epidemiological methods will be welcome if based on a biological application. It is important that manuscripts are of general interest, have a general applicability, and are not solely policy-oriented. Descriptive epidemiological studies, meta-analyses and studies providing information of geographically limited interest will not be considered. The journal welcomes review articles focusing on analyses of the mechanisms of host-microbe interactions including epidemiological studies. The articles should present comprehensive, critical summaries of current knowledge in the field and should not be limited to a discussion of the author's work. Thematic issues composed of solicited review articles are also published.Specific aspects of treatment of diseases, pathological and clinical studies (including case reports), diagnosis tests and technical reports, do not fall within the scope of the journal. Studies that are preliminary, of weak originality as well as negative results, are also not appropriate to the journal. Merely descriptive and correlative studies are not a priority. The journal is aimed at scientists working in research institutes, universities, governmental institutions or non-governmental organisations, private firms and the pharmaceutical industry.